In vitro efficacy of a 0.2% polyhexamethylene biguanide‐impregnated gauze dressing against pathogenic bacterial isolates found in horses. Issue 4 (30th March 2021) - Noll, Charlene V.; Kilcoyne, Isabelle; Nieto, Jorge E.; Thio, Timothy; Byrne, Barbara A.
Abstract: Objective: To determine the ability of 0.2% polyhexamethylene biguanide (PHMB)‐impregnated gauze to inhibit the growth of bacteria isolated from equine infected sites. Study Design: In vitro study. Methods: Nine bacterial isolates were obtained from cultures submitted from equine patients presenting with penetrating injuries of the hoof ( n = 4), septic osteitis ( n = 1), synovial sepsis ( n = 1), wounds ( n = 2), and incisional infection following laparotomy ( n = 1). Two standardized strains were also included. A standard inoculum of each isolate was placed on 12 Muller–Hinton agar plates. Squares (2.5 cm × 2.5 cm) of 0.2% PHMB‐impregnated ( n = 6) and nonimpregnated control gauze ( n = 6) were placed on inoculated agar plates. Bacterial growth under each gauze square was assessed after a 24‐h incubation period and areas of inhibition were measured to a standardized scale, using image‐processing software. Mean ± SD growth inhibition (%) using 0.2% PHMB‐impregnated gauze was compared to the nonimpregnated gauze for each isolate using Student's t test ( p < .05). Results: The 0.2% PMHB‐impregnated gauze inhibited the growth of Staphylococcus spp. ( n = 4) by 33%–83.1% and that of Escherichia coli spp. ( n = 4) by 6.5%–37%. There was no inhibition of growth of Pseudomonas aeruginosa or either Enterococcus spp. Conclusion: The 0.2% PHMB‐impregnated dressing tested here inhibited the growth of staphylococcal and E. coli isolates, but the magnitude of inhibition varied between strains. Clinical Relevance: These results justify in vivo studies to evaluate the ability of the dressing to reduce the bacterial growth of common equine bacterial pathogens in clinical practice.